A kind of corrosion-resistant concrete and its production process

By using specially made corrosion-resistant additives in concrete, a hydrated gel network on the aggregate surface is formed, which solves the problem of performance deterioration of existing concrete under corrosion, and significantly improves its corrosion resistance and service life.

CN119219392BActive Publication Date: 2025-02-18INNER MONGOLIA ROAD & BRIDGE ENG TECH INSPECTION CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411755157.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-02-18
Estimated Expiration
2044-12-03

AI Technical Summary

Technical Problem

The performance of existing concrete deteriorates under climate, physical and chemical corrosion, resulting in early failure and damage to the structure, and the existing anti-corrosion methods are complex, costly and uncontrollable.

Method used

Corrosion-resistant additives prepared from end-epoxy polyether silicone oil, chlorosulfonic acid and diethylene triamine are used to form block polymers by reacting with aggregates, which are preferred to adhere to the aggregate surface to form a hydrated gel Network, enhance the corrosion resistance of concrete.

Benefits of technology

It significantly improves the chloride ion and sulfate corrosion resistance of concrete, reduces the penetration of corrosive media, avoids cracking problems caused by premature hydration of concrete, and extends the service life of the structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to a corrosion-resistant concrete and a production process thereof, and belongs to the technical field of concrete. The concrete comprises, by weight, 100 parts of ordinary Portland cement, 215-242 parts of coarse aggregate, 105-137 parts of fine aggregate, 17-23 parts of ash, 1.5-2.1 parts of redispersible rubber powder, 2.2-2.9 parts of corrosion-resistant additive, 1.3-1.5 parts of water reducer and 42-48 parts of water; the corrosion-resistant additive is a polymer formed by the ring-opening reaction of diethylenetriamine and terminal epoxy polyether silicone oil to form a block, that is, an intermediate, and then chlorosulfonic acid replaces the active hydrogen of the hydroxyl group and the secondary amine group in the intermediate molecule to sulfonate the intermediate to form a sulfonate modification; the intermediate is attached to the surface of the aggregate to promote hydration during the mixing process, and forms an aggregate-hydration gel interwoven shielding net in the concrete to hinder the penetration of the corrosive medium, so that the concrete has excellent corrosion resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of concrete, and in particular relates to corrosion-resistant concrete and a production process thereof. Background Art

[0002] Concrete is the foundation of civil facilities systems worldwide and is the most widely used building material. It is highly favored for its mechanical strength, cost-effectiveness, impermeability and plasticity. Among them, reinforced concrete structures are widely used in infrastructure construction because they can simultaneously take advantage of the advantages of steel bars and concrete, have high strength, good fire resistance and weather resistance, low cost, and convenient construction. However, in actual use, due to factors such as climate, physical and chemical corrosion, the performance of concrete materials deteriorates or steel bars rust, making it impossible to ensure safety and applicability within the design service life and fail prematurely; after the durability of reinforced concrete structures is damaged, a large amount of money needs to be spent on repairs, which will cause huge economic losses.

[0003] There are various anti-corrosion methods for concrete in the prior art, such as coating protection, which is to apply a corrosion-resistant coating to the surface of concrete buildings to prevent concrete from contacting with external corrosive media; another example is steel bar protection, which uses steel bars with anti-corrosion layers or sets up cathodic protection to reduce the corrosion of steel bars, thereby ensuring the stability of concrete buildings. These methods result in complex application procedures for concrete, high maintenance costs, and uncontrolled corrosion protection effects; improving the anti-corrosion performance of concrete itself is the best means to solve the problem of concrete anti-corrosion, such as using high-performance silicate cement to make concrete have higher density and lower porosity, which is an important direction for improving the corrosion resistance of concrete. However, the cost of high-performance silicate cement is relatively high and its application occasions are extremely limited. Based on this, in the prior art, by compounding hydration promoters into concrete to promote the formation of hydration gel in concrete, the density of concrete can be improved to a certain extent. However, the introduction of too much hydration promoter is likely to form stress cracks in concrete, which in turn aggravates corrosion and limits the improvement of the anti-corrosion performance of concrete. Summary of the invention

[0004] In order to solve the technical problems mentioned in the background technology, the purpose of the present invention is to provide a corrosion-resistant concrete and a production process thereof.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A corrosion-resistant concrete comprises, by weight, 100 parts of ordinary Portland cement, 215-242 parts of coarse aggregate, 105-137 parts of fine aggregate, 17-23 parts of ash, 1.5-2.1 parts of redispersible rubber powder, 2.2-2.9 parts of corrosion-resistant additive, 1.3-1.5 parts of water reducer and 42-48 parts of water.

[0007] The corrosion-resistant additive is prepared by the following method:

[0008] Step A1: Mix terminal epoxy polyether silicone oil, dibutyltin dilaurate and dioxane, introduce nitrogen protection, control the temperature of the water bath to 30-45°C, apply 90-150rpm stirring, slowly add diethylenetriamine to react for 2-3h, then continue to heat and reflux for 1.2-1.6h, and remove dioxane by vacuum rotary evaporation to obtain an intermediate;

[0009] Furthermore, the epoxy content of the terminal epoxy polyether silicone oil, the feed ratio of diethylenetriamine, dibutyltin dilaurate and dioxane is 0.1 mol: 55-60 mmol: 0.1-0.13 g: 150-200 mL, and the diethylenetriamine and the terminal epoxy polyether silicone oil are ring-opened to form a macromolecular compound.

[0010] Step A2: The intermediate, triethylamine and chloroform are mixed, and dry nitrogen is introduced for protection. The temperature is controlled at 0-10°C in an ice-water bath, and stirring is applied at 150-180 rpm. Chlorosulfonic acid is slowly added to react for 1-1.5 hours, and then the temperature is raised to 40-50°C, and clear lime water is added to adjust the pH value to 8-9. The mixture is allowed to stand for 12 hours, and chloroform is removed by rotary evaporation and dried to obtain a corrosion-resistant additive;

[0011] Furthermore, the dosage ratio of the intermediate, chlorosulfonic acid, triethylamine and chloroform is 50g:8-12mmol:1-1.5mL:55-70mL, and the chlorosulfonic acid replaces the active hydrogen of the hydroxyl group and the secondary amine group in the intermediate molecule to sulfonate the intermediate to form sulfonate modification.

[0012] Furthermore, the coarse aggregate is crushed stone with a particle size of 15-35 mm.

[0013] Furthermore, the fine aggregate is graded machine-made sand with a particle size of 1-5 mm.

[0014] Furthermore, the ash material is compounded by fly ash, slag powder, desulfurized gypsum powder and silica fume.

[0015] Furthermore, the water reducing agent is a polycarboxylic acid type water reducing agent.

[0016] A production process of corrosion-resistant concrete, comprising the following steps:

[0017] Step S1: mixing ordinary Portland cement, coarse aggregate, fine aggregate, ash and corrosion-resistant additive to prepare dry material;

[0018] Step S2: mixing the redispersible rubber powder, the water reducing agent and water to form a slurry;

[0019] Step S3: Add dry materials and add slurry at a uniform speed under stirring to obtain corrosion-resistant concrete.

[0020] Beneficial effects of the present invention:

[0021] The present invention is based on the traditional concrete formula, and the self-developed corrosion-resistant additive is compounded to give the concrete excellent corrosion resistance. The invention forms a block polymer, i.e., an intermediate, by the ring-opening reaction of diethylenetriamine and terminal epoxy polyether silicone oil. Then, chlorosulfonic acid replaces the active hydrogen of the hydroxyl group and the secondary amine group in the intermediate molecule, and the intermediate is sulfonated to form a sulfonate modification. The corrosion-resistant additive molecule contains a large number of organic silicon segments, so that its surface energy is relatively low, while the surface energy of cement particles is large. During the mixing process, the corrosion-resistant additive preferentially adheres to the surface of the aggregate with relatively low surface energy, and the polyether segments in the corrosion-resistant additive molecules form hydrophilic modification, which is easier to disperse during the mixing process, so that the corrosion-resistant additive is uniformly enriched on the aggregate surface. Then, the multi-nitrogen structure introduced by diethylenetriamine in the corrosion-resistant additive molecules forms a complexation, and captures calcium, aluminum, iron and other ions in the mixed system. , hydrated gel is preferentially formed near the surface of aggregates, and the sulfonate structure on the corrosion-resistant additive molecule can inhibit the precipitation and growth of calcium hydroxide crystals, especially between aggregates that are in contact or close to each other, it is easier to form fully hydrated gel, and an aggregate-hydrated gel interwoven network is formed in the early stage of hydration. The fully hydrated gel between aggregates forms a filling effect, which reduces the penetration of corrosive media from the gaps between aggregates. At the same time, the hydrated gel has a certain adsorption effect on chloride ions, and the interwoven network containing hydrated gel forms a large number of adsorption networks, which shield the penetration of chloride ions by adsorption, thereby making the concrete have excellent corrosion resistance; in addition, the corrosion-resistant additive is different from the existing hydration promoter. It is directionally enriched on the surface of aggregates instead of being free in concrete. Aggregate-hydrated gel construction can be formed at a lower dosage, avoiding cracking caused by premature hydration of concrete. DETAILED DESCRIPTION

[0022] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0023] Example 1, preparation of corrosion-resistant concrete, the specific implementation process is as follows:

[0024] (1) Preparation of corrosion-resistant additives

[0025] Step A1: Take terminal epoxy polyether silicone oil, dibutyltin dilaurate and dioxane, mix them, introduce nitrogen protection, control the temperature of the water bath to 45°C, apply 150rpm stirring, slowly add diethylenetriamine to react for 2h, and then continue to heat and reflux for 1.6h, wherein the terminal epoxy polyether silicone oil is selected from MY EES9KF type raw material, and the epoxy content of the terminal epoxy polyether silicone oil, diethylenetriamine, dibutyltin dilaurate and dioxane are in a feed ratio of 0.1mol:60mmol:0.13g:200mL. After the reaction is completed, the dioxane is quickly removed by reduced pressure rotary evaporation to obtain an intermediate.

[0026] Step A2: Take the intermediate, triethylamine and chloroform, mix them, pass dry nitrogen for protection, control the temperature at 10°C in an ice-water bath, apply stirring at 180rpm, slowly add chlorosulfonic acid to react for 1h, then raise the temperature to 50°C, add clear lime water to adjust the pH value to 9, and let it stand for 12h, wherein the dosage ratio of the intermediate, chlorosulfonic acid, triethylamine and chloroform is 50g:12mmol:1.5mL:70mL, remove chloroform by rotary evaporation and dry the rotary evaporation substrate to obtain a corrosion-resistant additive.

[0027] (2) Preparation of corrosion-resistant concrete

[0028] Step S1: The following raw materials are calculated by weight: 100 parts of ordinary Portland cement, commercially available P.O42.5 ordinary Portland cement is selected; 242 parts of coarse aggregate, commercially available crushed stone with a particle size of 15-35 mm is selected; 105 parts of fine aggregate, commercially available graded machine-made sand with a particle size of 1-5 mm is selected; 17 parts of ash material, fly ash, slag powder, desulfurized gypsum powder and silica fume are pre-mixed in a weight ratio of 1:0.35:0.25:0.1; 2.2 parts of corrosion-resistant additives are prepared in this embodiment; each raw material is added into a mixer and mixed at 30 rpm for 20 minutes to prepare a dry material.

[0029] Step S2: The following raw materials are calculated by weight: 1.7 parts of redispersible rubber powder, which is a commercially available HECOCELL® HK6659 raw material; 1.3 parts of water reducer, which is a commercially available GK-3000 raw material; and 42 parts of water. The raw materials are premixed into a uniform mixed liquid by stirring to prepare a slurry.

[0030] Step S3: Add the dry material into the mixer at once, stir at 30 rpm first, add the slurry at a uniform speed and stir for 10 minutes, then increase the stirring rate to 55 rpm and stir for 8 minutes to obtain corrosion-resistant concrete.

[0031] Example 2, preparing corrosion-resistant concrete, the specific implementation process is as follows:

[0032] (1) Preparation of corrosion-resistant additives

[0033] Step A1: Take terminal epoxy polyether silicone oil, dibutyltin dilaurate and dioxane, mix them, introduce nitrogen protection, control the temperature of the water bath to 30°C, apply 90rpm stirring, slowly add diethylenetriamine to react for 3 hours, and then continue to heat and reflux for 1.2 hours, wherein the terminal epoxy polyether silicone oil is selected from RH-NB-ES7K type raw material, and the epoxy content of the terminal epoxy polyether silicone oil, diethylenetriamine, dibutyltin dilaurate and dioxane are in a feed ratio of 0.1 mol: 55 mmol: 0.1 g: 150 mL. After the reaction is completed, the dioxane is quickly removed by reduced pressure rotary evaporation to obtain an intermediate.

[0034] Step A2: Take the intermediate, triethylamine and chloroform, mix them, pass dry nitrogen for protection, control the temperature at 0°C in an ice-water bath, apply stirring at 150rpm, slowly add chlorosulfonic acid to react for 1.5h, then raise the temperature to 40°C, add clear lime water to adjust the pH value to 8, and let it stand for 12h, wherein the dosage ratio of the intermediate, chlorosulfonic acid, triethylamine and chloroform is 50g:8mmol:1mL:55mL, remove chloroform by rotary evaporation and dry the rotary evaporation substrate to obtain a corrosion-resistant additive.

[0035] (2) Preparation of corrosion-resistant concrete

[0036] Step S1: The following raw materials are calculated by weight: 100 parts of ordinary Portland cement, commercially available P.O42.5 ordinary Portland cement is selected; 220 parts of coarse aggregate, commercially available crushed stone with a particle size of 15-35 mm is selected; 137 parts of fine aggregate, commercially available graded machine-made sand with a particle size of 1-5 mm is selected; 23 parts of ash material, fly ash, slag powder, desulfurized gypsum powder and silica fume are pre-mixed in a weight ratio of 1:0.4:0.15:0.13; 2.9 parts of corrosion-resistant additives are prepared in this embodiment; each raw material is added into a mixer and mixed at 30 rpm for 20 minutes to prepare a dry material.

[0037] Step S2: The following raw materials are calculated by weight: 2.1 parts of redispersible rubber powder, which is a commercially available HECOCELL® HK6659 raw material; 1.5 parts of water reducer, which is a commercially available GK-3000 raw material; and 48 parts of water. The raw materials are premixed into a uniform mixed liquid by stirring to prepare a slurry.

[0038] Step S3: Add the dry material into the mixer at once, stir at 30 rpm first, add the slurry at a uniform speed and stir for 10 minutes, then increase the stirring rate to 55 rpm and stir for 8 minutes to obtain corrosion-resistant concrete.

[0039] Example 3, preparation of corrosion-resistant concrete, the specific implementation process is as follows:

[0040] (1) Preparation of corrosion-resistant additives

[0041] Step A1: Take terminal epoxy polyether silicone oil, dibutyltin dilaurate and dioxane, mix them, introduce nitrogen protection, control the temperature of the water bath to 38°C, apply stirring at 120rpm, slowly add diethylenetriamine to react for 1.5h, and then continue to heat and reflux for 1.3h, wherein the terminal epoxy polyether silicone oil is selected from RH-NB-ES10K type raw material, and the epoxy content of the terminal epoxy polyether silicone oil, diethylenetriamine, dibutyltin dilaurate and dioxane are in a feed ratio of 0.1mol:58mmol:0.11g:170mL. After the reaction is completed, the dioxane is quickly removed by reduced pressure rotary evaporation to obtain an intermediate.

[0042] Step A2: Take the intermediate, triethylamine and chloroform, mix them, pass dry nitrogen for protection, control the temperature at 5°C in an ice-water bath, apply stirring at 180rpm, slowly add chlorosulfonic acid to react for 1.2h, then raise the temperature to 45°C, add clear lime water to adjust the pH value to 9, and let it stand for 12h, wherein the dosage ratio of the intermediate, chlorosulfonic acid, triethylamine and chloroform is 50g:10mmol:1.3mL:60mL, remove chloroform by rotary evaporation and dry the rotary evaporation substrate to obtain a corrosion-resistant additive.

[0043] (2) Preparation of corrosion-resistant concrete

[0044] Step S1: The following raw materials are calculated by weight: 100 parts of ordinary Portland cement, commercially available P.O42.5 ordinary Portland cement is selected; 225 parts of coarse aggregate, commercially available crushed stone with a particle size of 15-35 mm is selected; 120 parts of fine aggregate, commercially available graded machine-made sand with a particle size of 1-5 mm is selected; 20 parts of ash material, fly ash, slag powder, desulfurized gypsum powder and silica fume are pre-mixed in a weight ratio of 1:0.35:0.15:0.13; 2.5 parts of corrosion-resistant additives are prepared in this embodiment; each raw material is added into a mixer and mixed at 30 rpm for 20 minutes to prepare a dry material.

[0045] Step S2: The following raw materials are calculated by weight: 1.9 parts of redispersible rubber powder, which is a commercially available HECOCELL® HK6659 raw material; 1.4 parts of water reducer, which is a commercially available GK-3000 raw material; and 45 parts of water. The raw materials are premixed into a uniform mixed liquid by stirring to prepare a slurry.

[0046] Step S3: Add the dry material into the mixer at once, stir at 30 rpm first, add the slurry at a uniform speed and stir for 10 minutes, then increase the stirring rate to 55 rpm and stir for 8 minutes to obtain corrosion-resistant concrete.

[0047] Example 4, preparation of corrosion-resistant concrete, the specific implementation process is as follows:

[0048] (1) Preparation of corrosion-resistant additives

[0049] Step A1: Take terminal epoxy polyether silicone oil, dibutyltin dilaurate and dioxane, mix them, introduce nitrogen protection, control the temperature of the water bath to 40°C, apply stirring at 150rpm, slowly add diethylenetriamine to react for 2.2h, and then continue to heat and reflux for 1.4h, wherein the terminal epoxy polyether silicone oil is selected from RH-NB-ES10K type raw material, and the epoxy content of the terminal epoxy polyether silicone oil, diethylenetriamine, dibutyltin dilaurate and dioxane are in a feed ratio of 0.1mol:60mmol:0.11g:180mL. After the reaction is completed, the dioxane is quickly removed by reduced pressure rotary evaporation to obtain an intermediate.

[0050] Step A2: Take the intermediate, triethylamine and chloroform, mix them, pass dry nitrogen for protection, control the temperature at 5°C in an ice-water bath, apply stirring at 180rpm, slowly add chlorosulfonic acid to react for 1.2h, then raise the temperature to 50°C, add clear lime water to adjust the pH value to 8, and let it stand for 12h, wherein the dosage ratio of the intermediate, chlorosulfonic acid, triethylamine and chloroform is 50g:11mmol:1.4mL:70mL, remove chloroform by rotary evaporation and dry the rotary evaporation substrate to obtain a corrosion-resistant additive.

[0051] (2) Preparation of corrosion-resistant concrete

[0052] Step S1: The following raw materials are calculated by weight: 100 parts of ordinary Portland cement, commercially available P.O42.5 ordinary Portland cement is selected; 215 parts of coarse aggregate, commercially available crushed stone with a particle size of 15-35 mm is selected; 113 parts of fine aggregate, commercially available graded machine-made sand with a particle size of 1-5 mm is selected; 21 parts of ash material, fly ash, slag powder, desulfurized gypsum powder and silica fume are pre-mixed in a weight ratio of 1:0.4:0.15:0.1; 2.7 parts of corrosion-resistant additives are prepared in this embodiment; each raw material is added into a mixer and mixed at 30 rpm for 20 minutes to prepare a dry material.

[0053] Step S2: The following raw materials are calculated by weight: 1.5 parts of redispersible rubber powder, which is a commercially available HECOCELL® HK6659 raw material; 1.4 parts of water reducer, which is a commercially available GK-3000 raw material; and 45 parts of water. The raw materials are premixed into a uniform mixed liquid by stirring to prepare a slurry.

[0054] Step S3: Add the dry material into the mixer at once, stir at 30 rpm first, add the slurry at a uniform speed and stir for 10 minutes, then increase the stirring rate to 55 rpm and stir for 8 minutes to obtain corrosion-resistant concrete.

[0055] Comparative Example 1

[0056] This comparative example is a blank control. Referring to Example 3, no corrosion-resistant additive is added during the implementation process, and the rest of the implementation process is exactly the same.

[0057] Comparative Example 2

[0058] This comparative example refers to Example 3, except that the corrosion-resistant additive is replaced with calcium formate in the same weight portion, and the rest of the implementation process is exactly the same.

[0059] The concrete prepared as above was poured into a mold and cured for 28 days before demolding and sampling. The samples were subjected to chloride ion penetration test and sulfate corrosion resistance test according to GB / T 50082-2009 standard. The concrete was poured into a square mold and cured for 56 days before crack resistance test. The specific test results are shown in Table 1:

[0060] Table 1

[0061]

[0062] It can be seen from the test data in Table 1 that the concrete prepared in the example has excellent resistance to chloride ion and sulfate corrosion and is not prone to cracking.

[0063] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0064] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A corrosion-resistant concrete, characterized in that: The composition includes, by weight: 100 parts of ordinary Portland cement, 215-242 parts of coarse aggregate, 105-137 parts of fine aggregate, 17-23 parts of ash, 1.5-2.1 parts of redispersible rubber powder, 2.2-2.9 parts of corrosion resistant additive, 1.3-1.5 parts of water reducer and 42-48 parts of water; The corrosion-resistant additive is prepared by the following method: Step A1: mixing terminal epoxy polyether silicone oil, dibutyltin dilaurate and dioxane, introducing nitrogen protection, controlling the temperature in a water bath at 30-45° C., stirring and slowly adding diethylenetriamine to react for 2-3 hours, then continuing to heat and reflux for 1.2-1.6 hours, and removing dioxane by reduced pressure rotary evaporation to obtain an intermediate, wherein the epoxy content of the terminal epoxy polyether silicone oil, diethylenetriamine, dibutyltin dilaurate and dioxane are in a feed ratio of 0.1 mol: 55-60 mmol: 0.1-0.13 g: 150-200 mL; Step A2: The intermediate, triethylamine and chloroform are mixed, and dry nitrogen is introduced for protection. The temperature is controlled at 0-10°C in an ice-water bath. Chlorosulfonic acid is slowly added with stirring for 1-1.5h, and then the temperature is raised to 40-50°C. Clear lime water is added to adjust the pH value to 8-9, and the mixture is allowed to stand for 12h. Chloroform is removed by rotary evaporation and dried to obtain a corrosion-resistant additive, wherein the intermediate, chlorosulfonic acid, triethylamine and chloroform are used in a feed ratio of 50g:8-12mmol:1-1.5mL:55-70mL; The ash material is compounded from fly ash, slag powder, desulfurized gypsum powder and silica ash.

2. The corrosion-resistant concrete according to claim 1, characterized in that: The coarse aggregate is crushed stone with a particle size of 15-35mm.

3. The corrosion-resistant concrete according to claim 1, characterized in that: The fine aggregate is graded machine-made sand with a particle size of 1-5 mm.

4. The corrosion-resistant concrete according to claim 1, characterized in that: The water reducing agent is a polycarboxylic acid type water reducing agent.

5. A production process for corrosion-resistant concrete according to any one of claims 1 to 4, characterized in that: Including the following processes: Step S1: mixing ordinary Portland cement, coarse aggregate, fine aggregate, ash and corrosion-resistant additive to prepare dry material; Step S2: mixing the redispersible rubber powder, the water reducing agent and water to form a slurry; Step S3: adding the dry material to the slurry at a uniform speed and mixing under stirring to obtain corrosion-resistant concrete.

Citation Information

Patent Citations

  • Corrosion resistant thermal spraying hole sealing agent and application method thereof

    CN104804614A

  • Corrosion-resistant impervious concrete material and preparation method thereof

    CN113754387A